Pengaruh Brand Image, Persepsi Harga, Cita Rasa terhadap Loyalitas Konsumen: Studi Kasus Sate Ayam Pak Siboen Kota Kediri - Gogot Saputro; Ahmad Idris; Dadang Afrianto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to examine the influence of Brand Image, price perception, and taste on customer loyalty at Sate Ayam Pak Siboen, a culinary business in Kediri City. A quantitative method with a causal approach was applied, involving 140 respondents who had made repeat purchases. Data were collected using structured questionnaires. The results of multiple linear regression analysis indicate that Brand Image, price perception, and taste each have a positive and significant effect on customer loyalty, both partially and simultaneously. These findings highlight the need for businesses to consistently maintain brand strength, fair pricing, and product taste quality to foster customer loyalty.